End-Stage Renal Failure Is an Independent Risk Factor for 1-Year Mortality After Hip Fracture Surgery. (16th April 2018) - Lo, Louise Woon Theng; Yanling, Xu; Chou, Andrew Chia Chen; Howe, Tet Sen; Allen, John Carson; Koh, Joyce Suang Bee
Introduction: End-stage renal failure (ESRF) with its associated comorbidities increase postoperative mortality in hip fracture patients. This study investigated the association of ESRF with various comorbidities in patients on dialysis and assessed rates ESRF as an independent risk factor for all-cause postoperative 1- year mortality rates. Methods: This was a retrospective cohort study on patients aged 55 years and older who underwent their first nonpathological, low-energy hip fracture surgery at an Asian tertiary hospital from June 2007 to 2012. Patients were identified as cases with ESRF on dialysis (study group) or non-ESRF patients (controls). Various comorbidity factors and postoperative 1-year mortality status were obtained from institutional electronic medical records. Univariate and multivariate logistic regression were used to identify significant risk factors for all-cause, 1-year mortality. Results: With no loss to follow-up, the 1-year postoperative mortality rate was 19.6% for the 46 patients with ESRF on dialysis and 8.4% for non-ESRF controls ( P = .028). Fisher exact test showed that hypertension, ischemic heart disease (IHD), diabetes mellitus (DM), anemia, cerebrovascular disease, and vascular disease were significantly associated with ESRF ( P < .05). Multivariable logistic regression analysis identified ESRF (adjusted odds ratio[AOR] = 2.85, P = .021), cancer (AOR = 3.04, P = .003), IHD (AOR = 2.07, P = .020), DM (AOR = 2.03, P = .022), and age (AOR = 1.08, P <.0001) as independent risk factors for 1-year mortality following hip fracture surgery. The area under the receiver–operating characteristic curve (95% confidence interval) for the multivariable predictor of 1-year mortality was 0.75 (0.60-0.82). Conclusions: Although associated with multiple comorbidities, ESRF was found to be independently predictive of 1-year mortality in patients undergoing hip fracture surgery, second to cancer in terms of magnitude of risk posed. As ESRF is a negative prognostic factor for 1-year mortality after hip fracture surgery, its importance should be recognized with implications on preoperative counseling to patients about the increased risk and implications on fracture prevention.